ANALISIS GAYA BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS V SD - Tri Astari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
This study aims to analyze the learning style of the mathematics learning outcomes in the fifth grade students of SD Negeri 064036 Medan. The type of this research is qualitative descriptive. The population and sample of this research is thirty two students of the fifth grade. The result of data analysis obtained there were twenty two students (68,75%) who have visual learning style, six students (18,75%) have auditory learning style, and four students (12,5%) with kinesthetic learning style. Many students who complete their learning outcomes (beyond the limits of KKM ≥ 68,5) by using test results on Fractional Subject as the test is six visual people (18,75%) with the average of students’ learning style 75,17; two auditory people (6,25%) with the average of students’ learning 72,50; and two kinesthetic people (6,25%) with the average of students’ learning style 73,00. Based on the result of data analysis, the learning style influences mathematics learning result.